Sistem Prediksi Pertandingan Sepak Bola Dengan Metode Analytical Hierarchy Process (AHP) - Daniel Walangare; Rosa Delima; Restyandito Restyandito (Universitas Kristen Duta Wacana, 2013)
The problem addressed in this research is how to predict the winner of football match with various criteria. The problem will be solved using Analytic Hierarchy Process (AHP) method. The AHP method that implemented to solve the problems will run two analysis to get an alternative solution. The first AHP method is criteria analysis, in order to get priority vector value. In criteria analysis, to know the consistency of criteria value filling, CR < 10%. If known that criteria value filling not consistant, the process must be repeated until CR < 10%. Then continue with alternate analysis to get global priority vector value wich is AHP solution. The accuration of this system is close to 80% compare with the real condition.